2022
DOI: 10.3350/cmh.2022.0039
|View full text |Cite
|
Sign up to set email alerts
|

Gut-derived lipopolysaccharide promotes alcoholic hepatosteatosis and subsequent hepatocellular carcinoma by stimulating neutrophil extracellular traps through toll-like receptor 4

Abstract: Background/Aims: Binge drinking leads to many disorders, including alcoholic hepatosteatosis, which is characterized by intrahepatic neutrophil infiltration and increases the risk of hepatocellular carcinoma (HCC). Molecular mechanisms may involve the migration of bacterial metabolites from the gut to the liver and the activation of neutrophil extracellular traps (NETs).Methods: Serum samples from both binge drinking and alcohol-avoiding patients were analyzed. Mouse models of chronic plus binge alcohol-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Indeed, in vivo and in vitro studies have shown that TLRs are key mediators in bacteria-triggered cancer. Lipopolysaccharide (LPS) derived from GM could induce hepatocellular carcinoma by activating TLR4 in immune cells ( Liu et al, 2022 ). Similarly, Ochi et al (2012) found that TLR4 was a key factor mediating carcinogenesis from pancreatic inflammatory disease to pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in vivo and in vitro studies have shown that TLRs are key mediators in bacteria-triggered cancer. Lipopolysaccharide (LPS) derived from GM could induce hepatocellular carcinoma by activating TLR4 in immune cells ( Liu et al, 2022 ). Similarly, Ochi et al (2012) found that TLR4 was a key factor mediating carcinogenesis from pancreatic inflammatory disease to pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 42 44 However, our study suggests that flagellin-mediated activation of TLR5 may be tumor suppressive, similar to accounts of TLR2 signaling 45 , 46 when compared with the many studies that demonstrate LPS-TLR4 signaling to promote HCC. 42 , 47 , 48 Notably, a single-nucleotide polymorphism of the TLR5 gene in humans was recently uncovered that affected immune responses to flagellin and was associated with steatohepatitis-dependent HCC. 49 Considering that regulation of the gut microbiota is predominately mediated by basolateral expression of TLR5 on intestinal epithelia, 26 , 50 future studies should explore how tissue-specific disruption of Tlr5 (ie, liver vs. intestine) impacts the gut microbiota and HCC progression in Fxr KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although most alcohol-associated liver disease can be achieved in animals by altering stimulating factors and experimental animals, it is currently difficult to establish animal models of alcohol-triggered HCC that can reproduce pathophysiological processes similar to those of human HCC [ 206 , 207 ]. As a precarcinogen, alcohol-induced liver inflammation and the related oxidative stress can cause DNA damage in liver cells [ 208 ].…”
Section: Discussionmentioning
confidence: 99%